2006
DOI: 10.1021/bi0606546
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylglucoside Exists as a Single Molecular Species with Saturated Fatty Acyl Chains in Developing Astroglial Membranes

Abstract: We previously found that phosphatidylglucoside (PtdGlc), a novel glycolipid expressed in HL60 cells, plays a role in forming signaling microdomains involved in cellular differentiation. Because cells contain minute levels of PtdGlc, pure PtdGlc is very difficult to isolate. Thus, its complete structure has never been assessed. To aid in analyzing PtdGlc, we generated a PtdGlc-specific monoclonal antibody, DIM21, by immunizing mice with detergent-insoluble membranes isolated from HL60 cells [Yamazaki, Y., et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Acetylated PtdGlc (1-stearyl-2-arachidoyl-sn-glycerol-3-phosphoryl β-D-(6-O-acetyl)glucopyranoside) also exists in fetal rat brain [134] (Fig. 4).…”
Section: Chemical Structure and Properties Of Ptdglcmentioning
confidence: 99%
“…Acetylated PtdGlc (1-stearyl-2-arachidoyl-sn-glycerol-3-phosphoryl β-D-(6-O-acetyl)glucopyranoside) also exists in fetal rat brain [134] (Fig. 4).…”
Section: Chemical Structure and Properties Of Ptdglcmentioning
confidence: 99%
“…Phosphatidyl-b-D-glucoside {PtdGlc [2-O-arachidoyl-1-O-(1-stearoyl)-sn-glycer-3-yl]-b-D-glucopyranosyl phosphate; fig. S1A} is a membrane glycerophospholipid (3) that is localized to radial glia and nascent astrocytes (4,5). We showed that PtdGlc and its hydrolytic derivative lyso-phosphatidyl-b-D-glucoside (LysoPtdGlc; fig.…”
mentioning
confidence: 99%
“…Mouse anti-PtdGlc IgM DIM21 and mouse anti-LacCer IgM T5A7 were prepared as described (5,17,19). Mouse anti-human Fas (CD95) IgM CH-11 and IgG ZB4 were obtained from Medical and Biological Laboratories (Nagoya, Japan).…”
Section: Abs and Other Reagentsmentioning
confidence: 99%
“…Reduction of endogenous cholesterol with methyl-b-cyclodextrin suppresses anti-PtdGlc Ab-stimulated tyrosine phosphorylation, resulting in the up-and downregulation of CD38 and c-Myc expression, respectively (16). Therefore, PtdGlc may form functional raft-like domains on the plasma membranes of HL-60 cells, although it does not have C24 fatty acid chains (17). PtdGlc forms distinct lipid domains from sphingolipids on the outer leaflet of the plasma membrane of HL-60 cells (18).…”
mentioning
confidence: 99%